TRAINING AGROFORESTRI SEBAGAI UPAYA MITIGASI PEMANASAN GLOBAL AKIBAT AKTIVITAS ANTROPOGENIK PERSPEKTIF AL-QUR’AN DI ISLAMIC SCHOOL CILODONG DEPOK - A. Juraidi; Novia Nurfadila; Ahmad Zain Sarnoto; Sunarto Sunarto; Abd. Aziz; Nurcholik Ahmad (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Agroforestry can be considered as a mitigation solution for global warming in accordance with the teachings of the Qur'an, which advocate for environmental preservation and prohibit harm to it. Global warming occurs due to the greenhouse effect, characterized by an increase in the concentration of greenhouse gases such as carbon dioxide (CO2), methane (CH4), and other gases in the atmosphere. The causes can be attributed to anthropogenic activities, such as excessive use of fossil fuels, forest degradation, overuse of chemical fertilizers, waste incineration, industrial activities, motor vehicle emissions, and electricity production. This article will elucidate the process of global warming, anthropogenic activities as its causes, and the role of agroforestry in reducing the impact of global warming by referencing the principles of the Qur'an through a literature review. Consequently, it is hoped that agroforestry can be implemented as a mitigation step for global warming in alignment with the values of the Qur'an, addressing the consequences of anthropogenic activities